Kesiapan Menikah dalam Perspektif Psikologi Pendidikan Islam: Telaah Konseptual tentang Kematangan Pribadi dan Kehidupan Keluarga - Jumingan Jumingan; Siti Rohimah (Lembaga Yasin AlSys, 2026)
Marriage readiness is an important issue in Islamic educational psychology because it is related to individual maturity, family well-being, and social stability. Although studies on marriage have been widely conducted from sociological and religious perspectives, conceptual discussions of marriage readiness through the lens of Islamic educational psychology, with an emphasis on personal maturity, remain limited. This study aims to analyze the concept of marriage readiness within the framework of Islamic educational psychology, particularly in the dimension of personal maturity and its implications for family life. This study used a qualitative approach with a library research design through a review of primary and secondary sources in the form of books, scientific journals, and relevant Islamic literature. Data were collected through documentation techniques and analyzed using content analysis and thematic analysis. The results showed that marriage readiness in Islamic educational psychology encompasses emotional, spiritual, intellectual, and social maturity that are interconnected and mutually reinforcing. Personal maturity functions as the main foundation for forming a harmonious, sakinah, mawaddah, and rahmah family. These findings contribute to the development of the concept of Islamic educational psychology and expand understanding of marriage preparation in the Islamic context. The conclusion of this study affirms that holistic personal maturity is a fundamental aspect in realizing a quality and sustainable family life. The implications of this study include theoretical contributions to the literature on family psychology and Islamic education, as well as practical implications for educational institutions, Islamic counseling, and family policymakers in developing marriage preparation programs based on Islamic values.